Anxiety Level of An Indonesian EFL Student in A Public Speaking Class: A Narrative Inquiry - Nur Mahmudi; Mirjam Anugerahwati (International Journal of Language Teaching and Education, 2021)
This research was designed to explore the anxiety level of an Indonesian EFL student in a public speaking class and how the study participant anticipates his anxiety in a public speaking class. Situated in an English course in East Java, the present study employed narrative inquiry for the data collection. The data were garnered through semi-structured interviews with the participant. The data analysis followed the three-dimensional space of narrative inquiry. Findings revealed three kinds of anxiety experienced by the participating student in his public speaking class such as trait anxiety, situational-specific anxiety, and state anxiety. The study also documented that the causes of speaking anxiety were communication apprehension, test anxiety, and fear of negative evaluation. This paper ends with suggestions for future research directions on anxiety issues in second language learning.